MYTH AND FOLKLORE EMBODIMENT IN THE FEMALE PROTAGONISTS OF CONTEMPORARY FICTIONS: A READING OF THE SHIVA TRILOGY AND BULBBUL - PRASADITA L RAVEENDRAN (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
The collective consciousness of a community is tremendously shaped by myths and folktales passed on from generation to generation. With the publication of Joseph Campbell's book The Hero with a Thousand Faces, the idea of the hero and his journey took a giant leap, allowing the commoner's life narratives to be equated with the mythical journey. This study analyzes how mythology is demythified and symbolically represented in two of India's famous narratives, a novel series Shiva Trilogy by Amish Tripathi and an “over-the-top” (OTT) film Bulbbul by Anvita Dutt. The objects of this research are Indian mythological narratives about Goddess Shakti and her various manifestations — Durga, Kali, Sati, and Parvati — whose respective nature and purpose differ vastly from one another. Through the qualitative research method, the paper shows that the reader/viewer has well-received the interweaving of myth with contemporary fiction. It has given way to a change in diegesis, from the predominantly male-hero-focused outline to a female-driven narrative. The myth-bound heroines thus represent the power to break the shackles of patriarchy and normative culture, allowing an area for women to radicalize themselves through bold actions. Kesadaran kolektif suatu komunitas sangat bergantung pada mitos dan cerita rakyat yang diturunkan dari generasi ke generasi. Dengan diterbitkannya The Hero with a Thousand Faces karya Joseph Campbell, gagasan tentang pahlawan dan perjalanannya memungkinkan narasi kehidupan orang biasa untuk disejajarkan dengan perjalanan mitos. Studi ini bertujuan untuk menganalisis bagaimana mitologi didemistifikasi dan secara simbolis direpresentasikan dalam dua narasi terkenal India, yakni serial novel Shiva Trilogy karya Amish Tripathi dan film “over-the-top” (OTT) Bulbbul karya Anvita Dutt. Objek penelitian ini adalah narasi mitologi India tentang Dewi Shakti dan berbagai manifestasinya — Durga, Kali, Sati, dan Parvati — yang sifat dan tujuannya masing-masing sangat berbeda satu sama lain. Melalui metode penelitian kualitatif, ditemukan; 1) pembaca/pemirsa telah menerima dengan baik jalinan mitos dengan fiksi kontemporer; 2) memberi jalan pada perubahan diegesis, dari garis besar yang berfokus pada pahlawan pria menjadi narasi yang digerakkan oleh wanita; 3) para tokoh wanita yang terikat mitos, mematahkan belenggu patriarki dan budaya normatif, memungkinkan area bagi perempuan untuk meradikalisasi diri mereka sendiri melalui tindakan yang berani.